GENDER IDENTITY IN YOUNG WOMEN PRACTICING PROSTITUTION - Cancio-Bello Ayes, Claudia (Revista Sexología y Sociedad, 2016)
THE RESEARCH ADDRESSES THE CHARACTERISTICS OF GENDER IDENTITY IN YOUNG WOMEN PRACTICING PROSTITUTION IN HAVANA, CUBA. THE RESEARCH PROBLEM WAS: WHAT CHARACTERISTICS HAS THE GENDER IDENTITY AS A COMPLEX MOTIVATIONAL DEVELOPMENT OF THE PERSONALITY IN A GROUP OF YOUNG WOMEN PRACTICING PROSTITUTION? THE GENERAL GOAL CONCERNING THE CHARACTERISTICS OF GENDER IDENTITY IN THESE SELECTED INDIVIDUALS DERIVED FROM IT. ANALYSIS DIMENSIONS OF GENDER IDENTITY AS A CATEGORY WERE: SELF-IMAGE, ASSESSMENT OF THE IMAGE, SELF-IDEAL, CONFLICTS, AND STRATEGIES FOR THE SOLUTION OF CONFLICTS. A QUALITATIVE METHODOLOGY AND THE METHOD OF STUDY OF MULTIPLE SAMPLES WERE IMPLEMENTED. THE SAMPLE INCLUDED SEVEN INDIVIDUALS, AND INTERVIEWS AND OBSERVATION WERE EMPLOYED AS TECHNIQUES. AS METHODS OF PROCESSING AND ANALYZING INFORMATION, THE CONTENTS ANALYSIS AND THE CASE DYNAMIC ANALYSIS WERE USED. MAIN RESULTS FOCUSED ON A TRADITIONAL SELF-IMAGE. THE ASSESSMENT OF SELF-IMAGE IS GENERALLY AMBIVALENT. ON THE ONE HAND, ACCORDING TO SELFIDEAL, THEY WISH TO BECOME SUCCESSFUL PROSTITUTES, BUT ON THE OTHER HAND THEY DESIRE TO BE GOOD MOTHERS AND WIVES. THESE NEEDS IN CONFLICT SHOW THAT BOTH ACCOMPLISH THE TRADITIONAL NORMS OF GENDER. AS STRATEGIES FOR THE SOLUTION OF CONFLICTS, THEY AGREED TO CONTINUE PRACTICING PROSTITUTION TO INCREASE THEIR ECONOMIC LEVEL, SATISFYING ONE OF THE NEEDS IMMEDIATELY AND LEAVING BEHIND THE OTHER FOR THE COMING FUTURE. KEY WORDS: GENDER IDENTITY, PROSTITUTION, WOMEN, YOUNG PEOPLE